Thermoelectric cooler performance enhancement using thermoelectric generators and their use as a single model to improve the performance of thermal battery management systems for electric vehicles - Hameed M.M.; Mansor M.; Azrin Mohd Azau M.; Muhsin S. (John Wiley and Sons Inc, 2024)
Conventional automobiles that operate on fossil fuels have recently been recognized as one of the significant contributors to environmental pollution, particularly given their increasing numbers in relation to the global population. Electric vehicle (EV) is considered as an excellent solution to this problem. The most difficult challenge is increasing the production of EVs using efficient and affordable batteries. All types of batteries used in EV have a power loss occurs in the form of temperature. The development of a battery thermal management system (BTMS) is a formidable obstacle. The new concept aims to improve the thermoelectric cooler (TEC) efficiency by integrating it with a thermoelectric generator (TEG), which is accomplished by fabricating a TEC-TEG model. The goal of combining a TEG and a TEC is to utilize waste heat generated on the TEC hot side and convert it into a stream that can be used to feed the TEC and increase its efficiency. Finally, the objectives of this paper are: To investigate the working principle of TEC-TEG model to regulate EV battery's temperature. To design a hybrid air-forced TEC-TEG model for EV batteries. To assess and verify the efficiency of a hybrid TEC-TEG model in regulating an EV battery temperature. 2022 John Wiley & Sons Ltd.